Critical thinking and judgment on engineer's work : its integration in engineering education - Giuliano, Gustavo (2022)
Fil: Giuliano, Gustavo. Pontificia Universidad Católica Argentina. Facultad de Ingeniería y Ciencias Agrarias; Argentina